Evaluation of the Impact of Effective Project Management Techniques on the Success of Steel Development Projects in Nigeria. (International Journal of Scientific Research and Management (IJSRM), 2025)
Purpose: This research sought to bridge the existing gap and also shed light on the challenges of project management techniques and their role in influencing success metrics in the steel development projects especially among rolling mills companies. Design/Methodology/Approach: The study adopted a systematic literature review approach. This involved a review of 25 articles sourced from various databases and repositories. The approved sources were then reviewed and thematic analysis used to identify the recurrent and meaningful themes. Findings/Conclusion: This research finds two noteworthy discoveries that bring distinctive insights to the literature on the variable application of Project Management Techniques throughout various phases of the project life cycle in steel development projects. It first confirms the contextual dependence of the usage of these techniques on various stages of the project life cycle. Recommendation: Steel development projects also involves numerous activities and there is need for project managers to integrate the useful techniques with project management software. The main aim of these software is to support project managers to handle various stages of a project. Suggestion for further studies: Future research studies should therefore explore the potential correlations between the use of specific project management techniques, whether certain techniques tend to be employed in conjunction with others, and whether their combined usage would possibly influence project success.